Interpretasi Makna Kalwedo sebagai Salam Persaudaraan di Maluku Barat Daya: Kajian Hermeneutika Gadamer - Misye Waliana; Elka Anakotta (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
Culture and traditions in Southwest Maluku contain a wealth of local wisdom that serves as a social glue, one of which is reflected in the use of the greeting Kalwedo. This greeting is not just a mere pleasantry, but has a very strong meaning in presenting the values ​​of brotherhood and local wisdom of the people of Southwest Maluku. This study shows several things, including, this study aims to interpret the antagonistic meaning of the greeting Kalwedo as a symbol of brotherhood by using the hermeneutic approach of Hans-Georg Gadamer. The research method used is qualitative descriptive-analysis. Data analysis was carried out through three hermeneutic movements, namely phenomenology, reconstruction, and dialogue. The results of the study show that Kalwedo contains the meaning of "we are together" or "we are one" which means emphasizing the unity of existence between the greeter and the greeted. Based on Gadamer's perspective, this meaning is formed from the fusion of horizons, namely between the past and the present, where the tradition will remain alive and meaningful in the contemporary context. The Kalwedo greeting serves as a medium for erasing barriers of difference, strengthening bonds of brotherhood, and building awareness of an inclusive collective identity. In conclusion, Kalwedo is a manifestation of wirkungsgeschichte (influential history) that continuously shapes and maintains social harmony amidst the dynamics of community life in Southwest Maluku.